2000
DOI: 10.1177/070674370004500705
|View full text |Cite
|
Sign up to set email alerts
|

The Clarke Institute Experience with Completed Suicide: 1966 to 1997

Abstract: Suicide as a cause ofdeath is one ofthe eventual outcomes ofmental illness, and the estimated risk ofsuicide for specific disorders is substantial, ranging from 4% to 10% for schizophrenia and up to 15% for severe affective disorders (1-6). The prevalence ofmental disorder in cases ofsuicide is 80% to 90% or higher (7-11). As a generalization, almost every substance abuse and severe mental disorder carries an increased risk of suicide (12,13). It will, therefore, inevitably be a cause of death in the caseload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A broad consensus exists in the literature supporting the hypothesis of a high prevalence of mental disorders among older adult cases of suicide (Kirsling, 1986; Martin, 2000; Miles, 1977; Osgood, 1985; Tanney, 1992; Zweig & Hinrichsen, 1993). It has been suggested that between 50% and 90% of older adults who committed suicide suffered from a psychiatric disorder, generally depression (Cattel, 1988; Conwell & Brent, 1995); however, the complex causal nature of the association between suicide and mental disorders is not clear.…”
mentioning
confidence: 99%
“…A broad consensus exists in the literature supporting the hypothesis of a high prevalence of mental disorders among older adult cases of suicide (Kirsling, 1986; Martin, 2000; Miles, 1977; Osgood, 1985; Tanney, 1992; Zweig & Hinrichsen, 1993). It has been suggested that between 50% and 90% of older adults who committed suicide suffered from a psychiatric disorder, generally depression (Cattel, 1988; Conwell & Brent, 1995); however, the complex causal nature of the association between suicide and mental disorders is not clear.…”
mentioning
confidence: 99%
“…Despite best efforts, suicides will still occur during psychiatric management of depressed patients [Martin, 2000]. Post-suicide management should include actively involving families and making referrals for available resources to help them deal with their loss.…”
Section: Postsuicide Managementmentioning
confidence: 99%
“…Interventions (or post‐ventions) following discharge from ‘secondary level’ health care services. Examples include reviewing the completed suicides from a single psychiatric facility (Martin 2001). …”
Section: The Emerging Model Of ‘The Trajectory Of Suicide’ (Adapted Fmentioning
confidence: 99%